Neurological signs and MRI findings in 12 dogs with multiple myeloma. Issue 4 (6th May 2019) - Wyatt, Sophie; De Risio, Luisa; Driver, Colin; José‐López, Roberto; Pivetta, Mauro; Beltran, Elsa
Abstract: Vertebral lesions and associated neurological signs occur in dogs with multiple myeloma, however, veterinary literature describing MRI findings is currently lacking. The objective of this multicenter, retrospective, case series study was to describe neurological signs and MRI findings in a group of dogs that presented for spinal pain or other neurological deficits and had multiple myeloma. Electronic records of four veterinary referral hospitals were reviewed. Dogs were included if they had a pathologically confirmed diagnosis of multiple myeloma, had presented for spinal pain or other neurological signs, and had undergone MRI of the vertebral column. The MRI studies were evaluated and the anatomical location of lesion(s), signal intensity, presence of extra‐dural material, degree of spinal cord compression, extent of vertebral lesions, and contrast enhancement were recorded. Twelve dogs met inclusion criteria. Most dogs (n = 8) had a chronic progressive history, with varying degrees of proprioceptive ataxia and paresis (n = 11), and spinal pain was a feature in all dogs. The MRI findings were variable but more consistent features included the presence of multiple expansile vertebral lesions without extension beyond the outer cortical limits of affected vertebrae, and associated extradural material causing spinal cord compression. The majority of lesions were hyper‐ to isointense on T2 (n = 12) and T1‐weighted (n = 8) sequences, with variable but homogeneous contrast‐enhancement (n = 12). These described MRI characteristics of multiple myeloma may be used to aid early identification and guide subsequent confirmatory diagnostic steps, to ultimately improve therapeutic approach and long‐term outcome.